2017
DOI: 10.1002/hed.24696
|View full text |Cite
|
Sign up to set email alerts
|

Nasal juvenile angiofibroma: Current perspectives with emphasis on management

Abstract: Juvenile angiofibroma is an uncommon, benign, locally aggressive vascular tumor. It is found almost exclusively in young men. Common presenting symptoms include nasal obstruction and epistaxis. More advanced tumors may present with facial swelling and visual or neurological disturbances. The evaluation of patients with juvenile angiofibroma relies on diagnostic imaging. Preoperative biopsy is not recommended. The mainstay of treatment is resection combined with preoperative embolization. Endoscopic surgery is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
135
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 105 publications
(149 citation statements)
references
References 143 publications
(221 reference statements)
3
135
0
11
Order By: Relevance
“…Current indications for follow‐up in patients treated for JA focus on early identification of persistent lesions in order to perform timely revision treatment, if dictated by the critical anatomic site of the lesion and/or the young age of the patient . On the other hand, no clear consensus exists about the duration of follow‐up .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current indications for follow‐up in patients treated for JA focus on early identification of persistent lesions in order to perform timely revision treatment, if dictated by the critical anatomic site of the lesion and/or the young age of the patient . On the other hand, no clear consensus exists about the duration of follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…This possibility has been first demonstrated by Kania et al by using CT with contrast medium, and confirmed in our most recent cases by performing early postoperative MRI with gadolinium enhancement. In patients with pJA on early postoperative imaging, the option to immediately perform revision surgery, which spares the patient more complex treatments in the future, should be considered . Moreover, it can be hypothesized that postpubertal patients with negative postoperative imaging will have a very low chance of developing a clinically relevant recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 It is thought that JNA originates from the posterosuperior margin of the sphenopalatine foramen. [1][2][3][4][5][6] Due to their anatomical location near the skull base and their tendency towards local invasion, these tumours tend to originate extensive tissue destruction, bone remodelling 6 and frequent recurrence. This growth pattern and spreading to local structures is unpredictable and at the time of diagnosis, most tumours are locally advanced.…”
Section: Introductionmentioning
confidence: 99%
“…2‐ More recently, transnasal endoscopic or endoscopic assisted approaches have become the standard of care . Preoperative selective embolization of feeding arteries has been used to decrease risk of intraoperative hemorrhage . Adjuvant radiotherapy has fallen out of favor due to the risk of pituitary damage and secondary malignancies but has been used in patients with no other options.…”
Section: Introductionmentioning
confidence: 99%